2012
DOI: 10.1155/2012/615476
|View full text |Cite
|
Sign up to set email alerts
|

Auricular Acupuncture May Suppress Epileptic Seizures via Activating the Parasympathetic Nervous System: A Hypothesis Based on Innovative Methods

Abstract: Auricular acupuncture is a diagnostic and treatment system based on normalizing the body's dysfunction. An increasing number of studies have demonstrated that auricular acupuncture has a significant effect on inducing parasympathetic tone. Epilepsy is a neurological disorder consisting of recurrent seizures resulting from excessive, uncontrolled electrical activity in the brain. Autonomic imbalance demonstrating an increased sympathetic activity and a reduced parasympathetic activation is involved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…Animal studies suggest that auricular acupuncture activates g-aminobutyric acid receptors, which reduces symptoms of morphine withdrawal, 16 and there is support for the hypothesis that opioid release stimulated by acupuncture helps to restore the release of dopamine. 17 In particular, auricular acupuncture potentially modifies autonomic dysfunction by increasing parasympathetic activity 18 and reduces sympathetic hyperactivity, 19 and stimulation of the liver 3 acupuncture point (LR 3; Tai Chong) activates several cortical and subcortical regions responsible for acute and chronic pain. 20 Recently, acupuncture treatment has been described as effective and safe in children 21 and newborns.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Animal studies suggest that auricular acupuncture activates g-aminobutyric acid receptors, which reduces symptoms of morphine withdrawal, 16 and there is support for the hypothesis that opioid release stimulated by acupuncture helps to restore the release of dopamine. 17 In particular, auricular acupuncture potentially modifies autonomic dysfunction by increasing parasympathetic activity 18 and reduces sympathetic hyperactivity, 19 and stimulation of the liver 3 acupuncture point (LR 3; Tai Chong) activates several cortical and subcortical regions responsible for acute and chronic pain. 20 Recently, acupuncture treatment has been described as effective and safe in children 21 and newborns.…”
Section: What This Study Addsmentioning
confidence: 99%
“…It is also found that the electrical stimulation of the ABVN is safe and well tolerated [38]. As a complementary method, it is also proposed that auricular acupuncture may suppress epileptic seizures via activating the parasympathetic nervous system [39–41]. …”
Section: Prevention and Treatment Of Diseases Via Vagal Regulationmentioning
confidence: 99%
“…Some studies including ours have been investigating the Deqi components using the quantitative measurements [2, 9, 10]. Auricular TENS instead of penetrating has been widely used to treat various disorders like drug addiction, cigarette addiction, mood disorders, obesity, pain, and many other conditions in clinical practice by stimulating points on the ear [15, 16]. However, the characteristics of Deqi upon auricular TENS are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…TENS on auricular points has been widely used to treat various disorders, for example, epileptic seizures and depression [15, 16]. However, the Deqi sensations of TENS on auricular points remain an ongoing area of research.…”
Section: Introductionmentioning
confidence: 99%